Proteomic analysis to investigate color changes of chilled beef longissimus steaks held under carbon monoxide and high oxygen packaging. (August 2018) - Yang, Xiaoyin; Wu, Shuang; Hopkins, David L.; Liang, Rongrong; Zhu, Lixian; Zhang, Yimin; Luo, Xin
Abstract: This study investigated the proteome basis for color stability variations in beef steaks packaged under two modified atmosphere packaging (MAP) methods: HiOx-MAP (80% O2 /20% CO2 ) and CO-MAP (0.4% CO/30% CO2 /69.6% N2 ) during 15 days of storage. The color stability, pH, and sarcoplasmic proteome analysis of steaks were evaluated on days 0, 5, 10 and 15 of storage. Proteomic results revealed that the differential expression of the sarcoplasmic proteome during storage contributed to the variations in meat color stability between the two MAP methods. Compared with HiOx-MAP steaks, some glycolytic and energy metabolic enzymes important in NADH regeneration and antioxidant processes, antioxidant peroxiredoxins (thioredoxin-dependent peroxide reductase, peroxiredoxin-2, peroxiredoxin-6) and protein DJ-1 were more abundant in CO-MAP steaks. The over-expression of these proteins could induce CO-MAP steaks to maintain high levels of metmyoglobin reducing activity and oxygen consumption rate, resulting in CO-MAP steaks exhibiting better color stability than HiOx-MAP steaks during storage.